2014
DOI: 10.1016/j.atmosenv.2013.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Observed and modeled ecosystem isoprene fluxes from an oak-dominated temperate forest and the influence of drought stress

Abstract: h i g h l i g h t sLocal constrained MEGAN tends to estimate isoprene emission reasonably well. Considerably high uncertainties were found for isoprene emission using Monte Carlo approach. Key uncertainty sources in isoprene emission estimated were identified. a r t i c l e i n f o a b s t r a c tWith local observed emission factor and meteorological data, this study constrained the Model of Emissions of Gases and Aerosols from Nature (MEGAN) v2.1 to estimate isoprene emission from the Dinghushan forest durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(170 citation statements)
references
References 53 publications
14
153
1
2
Order By: Relevance
“…Since the SW availability modulation (1 to 0) used in MEGAN was based on the single observation made by Pegoraro et al (2004) between Populus deltoids photosynthesis and stomatal conductance to water vapour, it is obviously not appropriate for water stress-resistant species. Such a 10 discrepancy under conditions other than Mediterranean was also noticed by Potosnak et al, 2014) during a seasonal study over a mixed broad-leaf forest mainly composed of Q. alba L.…”
Section: Towards What Isoprene Emission Modeling Improvement?mentioning
confidence: 85%
“…Since the SW availability modulation (1 to 0) used in MEGAN was based on the single observation made by Pegoraro et al (2004) between Populus deltoids photosynthesis and stomatal conductance to water vapour, it is obviously not appropriate for water stress-resistant species. Such a 10 discrepancy under conditions other than Mediterranean was also noticed by Potosnak et al, 2014) during a seasonal study over a mixed broad-leaf forest mainly composed of Q. alba L.…”
Section: Towards What Isoprene Emission Modeling Improvement?mentioning
confidence: 85%
“…The response of isoprene emissions to VPD is studied much less and not included in current biogenic emission algorithms. Isoprene emissions decrease drastically under severe drought conditions when soil moisture is below a threshold (21,32), confounding the relationship between isoprene emissions and VPD in field observations (20,21,36,37). However, a few studies reported that the current biogenic emission algorithm underestimates the enhanced isoprene emissions at the initial stage of a drought when large variation in ambient humidity occurred but the decrease in soil moisture was insignificant (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…2B). Enhanced isoprene emissions are likely due in part to increased leaf temperature and decreased internal CO 2 concentration, caused by reduced stomatal conductance under mild drought stress (20). More field and laboratory measurements are obviously required to quantify the response function of isoprene emission to short-term stress of high VPD and to understand the underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In their study the most emitted compounds were isoprene, methanol, acetone and methyl vinyl ketone + methacrolein. The high emissions can be explained by the ecosystem, as oaks are known to be strong isoprene emitters (e.g., Potosnak et al, 2014). Kaser et al (2013a) reported 8 h daytime fluxes only, so a direct comparison with the 24 h net flux from the other studies is not possible.…”
Section: Ec Voc Fluxes Above Different Ecosystemsmentioning
confidence: 99%